2008
DOI: 10.1002/ppul.20836
|View full text |Cite
|
Sign up to set email alerts
|

A drop in gas temperature in the external part of the endotracheal tube is problematic during neonatal respiratory support

Abstract: During neonatal respiratory support, maintaining optimal humidity minimizes the risk of airway occlusion and chronic lung disease. With neonatal respiratory support using a heated humidifier,condensation following decreases in temperature within the unheated part of the inspiratory circuit represents a serious problem, due to the resulting drop in absolute humidity. Several reports describing the temperature/humidity gradient in the unheated inspiratory limb have excluded the endotracheal tube (ETT). The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…Neonates might be particularly at risk because of their relatively small tidal volume. Even a small change in gas temperature inside the endotracheal tube can induce condensation of distilled water and rapidly trigger mucosal edema of the respiratory tract . Furthermore, even a mild stimulus, such as cold stimulation to facial skin, induces constriction of the bronchus, although its extent is milder than direct cooling …”
Section: Discussionmentioning
confidence: 99%
“…Neonates might be particularly at risk because of their relatively small tidal volume. Even a small change in gas temperature inside the endotracheal tube can induce condensation of distilled water and rapidly trigger mucosal edema of the respiratory tract . Furthermore, even a mild stimulus, such as cold stimulation to facial skin, induces constriction of the bronchus, although its extent is milder than direct cooling …”
Section: Discussionmentioning
confidence: 99%
“…In IPPV, the temperature drop in the external ETT is dependent on minute volumes; however, there have been no reports measuring the temperature drop in HFV. In the current study, we observed that the temperature in the ETT also decreased during HFV when the oscillatory volume (VThf) decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we observed that the temperature in the ETT also decreased during HFV when the oscillatory volume (VThf) decreased. In IPPV, the temperature decrease in the unheated ETT is lower when the minute volume (MV) is high than when the MV is low . In cases with a very low MV, the time required for inspired gas to reach the patient threshold is sufficiently long to allow the gas to approach environmental temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations